Efektivitas Pemberian Pisang Ambon Dengan Jus Tomat Terhadap Penurunan Tekanan Darah Pada Ibu Haml Dengan Hipertensi - Intan Nugraheni; Agustin Setianingsih; Farida Sukowati (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2022)
Maternal mortality in Indonesia is still dominated by bleeding, infection and hypertension. More than 25% of maternal deaths in Indonesia are due to hypertension. In Central Java Province, 32.97% of hypertension was ranked first as a case of maternal death. The purpose of this study was to determine the effectiveness of giving Tomato juice with Ambon banana to reduce blood pressure in pregnant women with hypertension. The research was conducted using an experimental research method, with a pretest-posttest control group design. The study population was all pregnant women with hypertension in the working area of the Semarang District Health Office as many as 68 pregnant women. The number of samples was 34 people for the treatment and control groups. The sampling technique used consecutive sampling. The research instrument used was a digital sphygmomanometer and a checklist. The results showed that the Paired t-test obtained p value 0.05, indicating that there was an effect of lowering blood pressure before and after being given tomato and banana juice for 7 days. The results of the Independent t-test showed that the difference in the average decrease in systolic blood pressure in the treatment group was more significant by 11.00 mmHg than in the control group by 4.61 mmHg and the average decrease in diastolic blood pressure in the treatment group was also more significant, namely equal to 6.08 mmHg compared to the control group at 4.31 mmHg. The result of p value difference between systolic and diastolic blood pressure is 0.001 and 0.007, which means Ha is accepted. Giving tomato juice is more effective in lowering blood pressure than giving Ambon banana. It is hoped that health workers will disseminate information to the public, especially pregnant women, to consume tomato juice as an effort to lower blood pressure.